Prevalence and Risk Factors of Type 2 Diabetes Mellitus among Depression Inpatients from 2005 to 2018 in Beijing, China - Peng Gao; Fude Yang; Qiuyue Ma; Botao Ma; Wenzhan Jing; Jue Liu; Moning Guo; Juan Li; Zhiren Wang; Min Liu (Health Data Science)
Background: There are few data on the comorbidity of diabetes in Chinese patients with depression. We aimed to calculate the prevalence and explore risk factors of type 2 diabetes mellitus (T2DM) among depression inpatients from 2005 to 2018 in Beijing. Methods: This study is a cross-sectional study. The data collected from 19 specialized psychiatric hospitals in Beijing were analyzed. The prevalence of T2DM and its distribution were analyzed. The multivariable logistic regression was performed to explore the risk factors of T2DM. Results: A total of 20,899 depression inpatients were included. The prevalence of T2DM was 9.13% [95% confidence interval (CI), 8.74% to 9.52%]. The prevalence of T2DM showed an upward trend with year (P for trend < 0.001) and age (P for trend < 0.001). The prevalence of T2DM was higher among readmitted patients (12.97%) and patients with comorbid hypertension (26.16%), hyperlipidemia (21.28%), and nonalcoholic fatty liver disease (NAFLD) (18.85%). The prevalence of T2DM in females was lower than in males among patients aged 18 to 59 years, while the prevalence of T2DM in females was higher than in males among patients aged ≥60 years. T2DM was associated with older age [adjusted odds ratios (aORs) ranged from 3.68 to 29.95, P < 0.001], hypertension (aOR, 3.01; 95% CI, 2.70 to 3.35; P < 0.001), hyperlipidemia (aOR, 1.69; 95% CI, 1.50 to 1.91; P < 0.001), and NAFLD (aOR, 1.58; 95% CI, 1.37 to 1.82; P < 0.001). Conclusions: The prevalence of T2DM among depression inpatients from 2005 to 2018 in Beijing was high and increased with the year. Depression inpatients who were older and with hypertension, hyperlipidemia, and NAFLD had a higher prevalence and risk of T2DM.